Company Performance Analysis Based On Financial Ratios Case Study At PT. Siantar Top, Tbk Period 2019-2023 - Muliyani, Muliyani; Sari, Indah Permata (Fin Sinergy: Jurnal Manajemen Keuangan, 2024)
The purpose of this study is to analyze the financial statements of PT. Siantar Top Tbk. in order to measure financial performance during the period 2019 to 2022. Financial performance can be measured by calculating financial ratios. This study uses descriptive quantitative data analysis techniques. Information data is used from the Indonesia Stock Exchange (IDX) website transparently. Financial ratios are the most appropriate method for measuring financial performance using the Liquidity Ratio, Solvency Ratio, Activity Ratio and Profitability Ratio. These four financial ratios can produce numbers, from the results it can be assessed whether the company is experiencing good or bad financial conditions. After conducting research, it was found that the Company's condition based on the profitability ratio was not good. The company has not been able to maintain the company's profit level, even the profit percentage tends to decrease every year. The company's management needs to determine a strategy to strengthen the company's performance or its stock performance so that it continues to improve in the future, sales are increased by paying attention to product quality, expanding the distribution network and creating quality products, and paying attention to production cost efficiency so that it can create good profits.